Antimicrobial Susceptibility of Escherichia coli and Salmonella spp. Isolates From Healthy Pigs in Australia: Results of a Pilot National Survey - Kidsley, Amanda K.; Abraham, Sam; Bell, Jan M.; O'Dea, Mark; Laird, Tanya J.; Jordan, David; Mitchell, Pat; McDevitt, Christopher A.; Trott, Darren J. (Frontiers in Microbiology, 2018)
This study investigated the frequency of antimicrobial non-susceptibility (defined as the frequency of isolates with minimum inhibitory concentrations above the CLSI susceptible clinical breakpoint) among E. coli and Salmonella spp. isolated from healthy Australian finisher pigs. E. coli (n=201) and Salmonella spp. (n=69) were isolated from cecal contents of slaughter-age pigs, originating from 19 farms distributed throughout Australia during July-December 2015. Isolates underwent minimum inhibitory concentration (MIC) susceptibility testing to 11 antimicrobials. The highest frequencies of non-susceptibility among respective isolates of E. coli and Salmonella spp. were to ampicillin (60.2% and 20.3%), tetracycline (68.2% and 26.1%), chloramphenicol (47.8% and 7.3%) and trimethoprim/sulfamethoxazole (33.8% and 11.6%). Four E. coli isolates had MICs above the wild-type epidemiological cut-off value for ciprofloxacin, with two isolates from the same farm classified as clinically resistant (MICs of >4µg/ml), a noteworthy finding given that fluoroquinolones (FQs) are not legally available for use in Australian food-producing animals. Three of these four E. coli isolates belonged to the sequence type (ST) 10, which has been isolated from both humans and production animals, whilst one isolate belonged to a new ST (7573) and possessed qnrS1. This study shows that non-susceptibility to first line antimicrobials is common among E. coli and Salmonella spp. isolates from healthy slaughter age pigs in Australia. However, very low levels of non-susceptibility to critically important antimicrobials (CIAs), namely third generation cephalosporins and fluoroquinolones were observed. Nevertheless, the isolation of two ciprofloxacin-resistant E. coli isolates from Australian pigs demonstrates that even in the absence of local antimicrobial selection pressure, fluoroquinolone-resistant E. coli clonal lineages may enter livestock production facilities despite strict biosecurity.